Introductory plant physiology - Noggle. G. Ray; Fritz, George J. (New Jersey : Prentice-Hall, Inc., 1983)
This book originated as a course in plant physiology for undergraduate students interested in higher plants and how they grow. Many of the students were majors in forestry, crop science, soil science, horticulture, or pest management and had a variety of backgrounds and training.
1. Introduction -- 2. The organization of plants -- 3. Cellular constituents and their biosynthesis -- 4. Respiration -- 5. Photophysiology -- 6. Photosynthesis -- 7. Photorespiration -- 8. Mineral nutrition -- 9. Assimilation of inorganic nutrients -- 10. Transport phenomena in plants: general considerations -- 11. Transport processes in plant cells and tissues -- 12. water as a plant constituent -- 13. The plant in relation to water -- 14. Plant growth substances: Structure and physiological effects -- 15. Plant growth substances: biosynthesis, analysis, transport, and mechanism of action -- 16. The physiology of seeds -- 17. Vegetative plant growth -- 18. Reproductive growth.
Includes index.
Keywords: PLANT -- PHYSIOLOGY